Bioimaging of mesenchymal stem cells spatial distribution and interactions with 3D In vitro tumor spheroids - Ferreira, Luís P. (2022)
In solid tumors, mesenchymal stem cells (MSCs) are recognized to establish complex intercommunication networks with cancer cells and to significantly influence their invasion and metastasis potential. Such bidirectional interplay occurs between both tissue resident/tumor-associated MSCs (TA-MSCs) and also tumor infiltrating MSCs (TM-MSCs) that migrate from distant sites such as the bone marrow. Interestingly, malignant cells interactions with MSCs in the tumor microenvironment extends beyond conventional exchanges of signaling factors and extracellular vesicles, including unconventional direct exchanges of intracellular components, or cancer cells cannibalism of MSCs. In the context of 3D in vitro tumor models, cell tracking assays making use of cell-labeling probes such as membrane penetrating dyes, can be leveraged to shed light on these events, and allow researchers to analyze overtime cell-to-cell spatial distribution, fusion, internal organization, and changes in co-cultured populations ratios. Herein, we describe a high-throughput compatible method through which MSCs positioning and permanence within in vitro 3D multicellular tumor spheroid models (3D-MCTS) can be tracked overtime. Although we have focused on the interactions of human bone marrow-derived MSCs (hBM-MSCs) within heterotypic lung cancer A549 3D-MCTS, these procedures can be implemented for other 3D tumor spheroid models and types of cells, taking into consideration that optimization steps are undertaken.